2016
DOI: 10.1038/srep35911
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Optical Absorption of Colloids of SiO2@Au and Fe3O4@Au Nanoparticles with Constraints

Abstract: We study the optical response of monodisperse colloids of core-shell plasmonic nanoparticles and introduce a computational approach to optimize absorption for photothermal applications that require dilute colloids of non-interacting particles with a prescribed volume fraction. Since the volume fraction is held constant, the particle concentration is size-dependent. Optimization is achieved by comparing the absorption spectra of colloids as a function of particle size and structure. We demonstrate the approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Also note, that for larger tuning capabilities, NPs with cores ranging between D C = 4-100 nm and shells up to 40 nm can also be prepared. [27][28][29][30][31] For the case of the dumbbell, Fe(Au) composites have been synthesised with minor modifications on the procedures of ref. 32.…”
Section: Synthesismentioning
confidence: 99%
“…Also note, that for larger tuning capabilities, NPs with cores ranging between D C = 4-100 nm and shells up to 40 nm can also be prepared. [27][28][29][30][31] For the case of the dumbbell, Fe(Au) composites have been synthesised with minor modifications on the procedures of ref. 32.…”
Section: Synthesismentioning
confidence: 99%
“…The monodispersed gold nanoparticles were used as labels to increase the sensitivity of the SPR imaging technique [10]. The amplification effect of antibody gold nanoparticles (AuNPs) and aptamer-AuNPs on the detection by SPR, and the development of a sandwich SPR method for protein detection, had been verified in previous research [2,3,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 90%
“…Applying Mie theory, the optical spectra of such hetero-structures were calculated for two different particle sizes, 60 and 100 nm, and various ratios between the shell thickness and the core radius, 10%, 20%, 30%, and 40%. The obtained spectra showed that the plasmonic absorption band is red-shifted as the ratio decreased [ 87 ]. This feature was confirmed experimentally by Canet-Ferrer et al [ 88 ], who evidenced that the extinction spectra of Fe 3 O 4 -Au core-shell NSs of 5 nm in diameter, exhibited the highest absorption wavelength (around 700 nm) when the gold thickness was the thinnest (about 1 nm).…”
Section: Magneto-plasmonic Properties Of Fanss and Afnssmentioning
confidence: 99%
“… Parametric analysis of optimum normalized absorption vs. λ for two different sized Fe 3 O 4 @Au NPS with various shell-to-radius ratios ξ Au ( a ) D p = 60 nm, ( b ) D p = 100 nm. Reproduced with permission from [ 87 ]. …”
Section: Figurementioning
confidence: 99%